Enhancement in resource allocation system for cloud environment using modified grey wolf technique - Soukaina Ouhame; Youssef Hadi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Cloud computing is new trend of technology which provides services with the help of internet based on specific rules.VM is one of the main elements of cloud computing it work on virtualizations concept. Due to the growth of cloud computing user demands for better service are increasing and it make different kind of issues in cloud environment. Data allocation sysytem in VM is one of them for that reason in this paper a new technique used for improvment of data allocation system in VM for cloud computing. The improvement took place GWO algorithm two main section of this algorithm are modified which are local search section and fitness function value. The above proposed technique used to improve three main parameter of scheduling which are energy consumption, throughput and average network executation time in VM for cloud computing. The proposed technique result are compare with ABC algorithm and GWO algorithm based on those result the proposed algorithm improved the three main parameter of load balancing technique in cloud computing.